SKRINING FITOKIMIA SERBUK DAUN PECUT KUDA DAN JAHE PUTIH SEGAR SEBAGAI BAHAN MINUMAN HERBAL - RIZKI NUGRAHANI; NI LUH PUTU SHERLY YUNIARTINI (GANEC SWARA, 2024)
Raw materials are something that is very important to prepare in order to get quality production results in terms of quality and benefits. The quality of raw materials needs to be considered both in terms of physical quality and in terms of nutritional content and chemical content. This study aims to determine the qualitative chemical content through phytochemical screening tests of herbal drink raw materials made from horse whip leaf simplicia in powder preparations with the addition of fresh white ginger rhizomes. This research is a descriptive-explorative research. This research process begins with drying the horse whip leaves and then converting them into powder. The research continued with soaking the horse whip leaf powder combined with fresh white ginger using methanol solvent and then phytochemical screening test. The results of phytochemical screening showed that the combined extract of horse whip leaves and fresh white ginger contained alkaloid, saponin, tannin, steroid and phenolic compounds.